PREVALENCE OF ZOONOTIC GASTROINTESTINAL HELMINTHS IN DOGS AND KNOWLEDGE OF RESIDENTS REGARDING GASTROINTESTINAL HELMINTHS IN NORTH BANK, MAKURDI - Ikye-Tor, Philomena; Anokwuru, Anthony; Per, Msugh; Ameh, Veronica; Ikye-Tor, Terungwa; Ishima, Lohodedoo (FUDMA Journal of Sciences, 2026)
Zoonotic gastrointestinal helminths (GIH) of dogs remain an important public health concern in developing countries due to poor sanitation, inadequate veterinary care, and increasing stray dog populations. This study assessed the prevalence of GIH among 384 dogs (193 household; 191stray) using saturated sodium chloride flotation and sedimentation techniques. Additionally, 116 dog owners were surveyed using structured questionnaires to evaluate their knowledge and preventive practices related to zoonotic GIH. Data was analyzed using descriptive statistics and Chi-square tests at a significance level of p < 0.05. Overall prevalence of GIH was 30.75%, with stray dogs (32.46%) slightly exceeding household dogs (29.02%). Six genera were identified: Ancylostoma spp. (13.02%), Toxocara spp. (10.94%), Dipylidium spp. (3.39%), Strongyloides spp. (2.34%), Echinococcus spp. (0.52%), and Trichuris spp. (0.52%). Ancylostoma spp. was more prevalent among strays, whereas Toxocara spp. predominated among household dogs. While age, sex and breed showed no significant associations with infection (p > 0.05), prevalence was significantly influenced by location and month of sampling; Ujam village (χ² = 23.46, p =0.0028) and month of June (χ² = 35.70, p = 0.0001) recorded the highest rates. Questionnaire survey findings indicated moderate awareness of zoonoses, yet revealed critical gaps regarding transmission routes and preventive practices. The study demonstrates that dogs in North Bank, Makurdi are important reservoirs of zoonotic GIH, posing substantial public health risks through environmental contamination. To mitigate these risks and protect the community, an integrated approach is recommended; routine deworming, improved environmental sanitation, public health campaigns, and responsible dog ownership.
Keywords: Zoonotic Helminths; Gastrointestinal Helminths; Dogs; Makurdi; Nigeria